2008
DOI: 10.1016/j.drugpo.2007.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and human rights imperatives to ensure medication-assisted treatment for opioid dependence in prisons and pre-trial detention

Abstract: Opioid dependence is a complex medical condition affecting neurocognitive and physical functioning. Forced or abrupt opioid withdrawal may cause profound physical and psychological suffering, including nausea, vomiting, diarrhoea, extreme agitation and/or anxiety. Opioid-dependent individuals are especially vulnerable at the time of arrest or initial detention, when they may, as a result of their chemical dependency, be coerced into providing incriminating testimony, or be driven to engage in risky behaviour (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Participants in our study also reported insomnia lasting for months and suicidal ideation. Similar findings were reported in another study, which suggested that “the trauma of imprisonment, coupled with severe opioid withdrawal, can also increase the risk of suicide in opioid dependent individuals with co-occurring disorders” (Bruce & Schleifer, 2008). Withdrawal symptoms, such as severe diarrhea and vomiting, could contribute to spread of infectious diseases (Mitchell et al,2009).…”
Section: Discussionsupporting
confidence: 87%
“…Participants in our study also reported insomnia lasting for months and suicidal ideation. Similar findings were reported in another study, which suggested that “the trauma of imprisonment, coupled with severe opioid withdrawal, can also increase the risk of suicide in opioid dependent individuals with co-occurring disorders” (Bruce & Schleifer, 2008). Withdrawal symptoms, such as severe diarrhea and vomiting, could contribute to spread of infectious diseases (Mitchell et al,2009).…”
Section: Discussionsupporting
confidence: 87%
“…Despite international guidelines recommending its provision, evidence-based treatment for opioid dependence, including opioid substitution therapy (OST) using methadone or buprenorphine, is only rarely available in prisons (Bruce & Schleifer, 2008). OST serves two key purposes, distinct but closely related.…”
Section: Discussionmentioning
confidence: 99%
“…Incarceration contributes more to adverse outcomes related to addiction and mental illness than to the transmission of infectious diseases. Although methadone is widely used to treat opioid addictions, few correctional facilities are willing to initiate or continue that treatment for inmates already on methadone upon entry (16, 34, 54, 60, 62, 70, 92), leaving the addicted subject to withdrawal during incarceration and more vulnerable to overdose upon release. Those with behavioral issues are more vulnerable to placement in “supermax” facilities, an environment particularly hazardous to the mentally ill (36, 69).…”
Section: Health In the Correctional Settingmentioning
confidence: 99%